Impact of insurance on survival in patients < 65 with head & neck cancer treated with radiotherapy. (13th November 2019) - Sittig, Mark P.; Luu, Michael; Yoshida, Emi J.; Scher, Kevin; Mita, Alain; Shiao, Stephen L.; Lu, Diana J.; Mallen‐St. Clair, Jon; Ho, Allen S.; Zumsteg, Zachary S.
Abstract: Objectives: The United States has a heterogenous health insurance landscape for patients <65 years. We sought to characterise the impact of primary payer on overall survival (OS) in insured patients younger than 65 with head and neck squamous cell carcinoma (HNSCC) treated with definitive radiotherapy. Design/Study/Participants: The National Cancer Database was queried for patients <65 years old diagnosed from 2004 to 2014 undergoing definitive radiotherapy ± chemotherapy for cancers of the nasopharynx, oropharynx, hypopharynx and larynx. Uninsured patients and oropharyngeal cancers without known HPV status were excluded. Main outcome: Overall survival. Results: Overall, 27 292 insured patients were identified, including 17 060 (62.5%) with private insurance. Median follow‐up was 52.1 months. In multivariable models, patients receiving Medicaid (HR = 1.66, 95% CI 1.57‐1.75, P < .001), Medicare (HR = 1.64, 95% CI 1.55‐1.73, P < .001) and other government insurance (HR = 1.44, 95% CI 1.29‐1., P < .001) had independently increased mortality in comparison to those with private insurance. In propensity score‐matched cohorts, 5‐year OS was 65.5% vs 50.6% for privately vs government‐insured patients, respectively ( P < .001). In multivariable subgroup analysis, private insurance was associated with improved survival in all subgroups. However, the magnitude of this effect was most pronounced in patients with HPV‐positive oropharyngeal cancer vs non‐HPV‐related cancer (interaction P < .001), younger patients (interaction P = .001), and those without comorbidity (interaction P < .001). Conclusions: Patients <65 with HNSCC undergoing definitive radiation with private health insurance have markedly longer survival relative to patients with government‐sponsored insurance. This illustrates that increasing access to care may be necessary, but is not sufficient, to mitigate the significant disparities in the US healthcare system.